1959
DOI: 10.1149/1.2427245
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Dispersion of Ultrasonic Waves

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
154
0
2

Year Published

1962
1962
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 383 publications
(158 citation statements)
references
References 0 publications
2
154
0
2
Order By: Relevance
“…Although a direct comparison of the obtained ultrasound absorption spectra was not possible, the comparison with the ultrasound velocity dispersion reported by Fukuda et al 18 1 This type of behavior has been observed in the past at similar temperatures for molecular organic liquids as well; 23,49,50,55 however, it should be noted that a separate determination of the shear viscosity behavior requires a separate study of the shear ultrasound wave because ultrasound relaxation spectra determined using a longitudinal wave are not suitable to investigate the microscopic origin of the shear viscosity (there are difficulties in the separation of the contributions of volume and shear viscosities to the ultrasonic relaxation). It is a general agreement that if α < α cl , the shear viscosity relaxation must be present.…”
Section: Measurement Results and Calculationsmentioning
confidence: 56%
See 4 more Smart Citations
“…Although a direct comparison of the obtained ultrasound absorption spectra was not possible, the comparison with the ultrasound velocity dispersion reported by Fukuda et al 18 1 This type of behavior has been observed in the past at similar temperatures for molecular organic liquids as well; 23,49,50,55 however, it should be noted that a separate determination of the shear viscosity behavior requires a separate study of the shear ultrasound wave because ultrasound relaxation spectra determined using a longitudinal wave are not suitable to investigate the microscopic origin of the shear viscosity (there are difficulties in the separation of the contributions of volume and shear viscosities to the ultrasonic relaxation). It is a general agreement that if α < α cl , the shear viscosity relaxation must be present.…”
Section: Measurement Results and Calculationsmentioning
confidence: 56%
“…In these highly attenuating conditions as well as in the border regions, particular care must be exercised because the relaxation processes cause not only absorption but also dispersion. 55,56 In the case of the four measured RTILs, the lowest f S8). Since (i) the relaxation frequency associated with the ultrasound absorption decreases with decreasing temperature (and vice versa), (ii) the α/α cl is small (in the range 1−3) and practically independent of temperature, and (iii) the temperature coefficient of ultrasound absorption is negative, the close similarity of ultrasound absorption in RTILs studied and associated molecular liquids is observed (the similarity was suggested already in our previous reports 1,2 ).…”
Section: Measurement Results and Calculationsmentioning
confidence: 89%
See 3 more Smart Citations